2009
DOI: 10.1111/j.1502-3885.2008.00074.x
|View full text |Cite
|
Sign up to set email alerts
|

Genesis of hummocks in glaciofluvial corridors near the Keewatin Ice Divide, Canada

Abstract: Glaciofluvial corridor hummocks (GCHs) within the Walker Lake map area, Canada, were examined in order to determine the character and genesis of these geomorphic features and their associated deposits. Located south of the Chantrey Moraine and north of the Keewatin Ice Divide, these corridors occur within a belt extending approximately 120 km east-west and approximately 60 km north-south. They are spaced 5-10 km apart and are hundreds of metres to several kilometres in width. They have undulating longitudinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
46
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(54 citation statements)
references
References 32 publications
7
46
0
Order By: Relevance
“…Another feature developed by subglacial meltwater are glaciofluvial corridors or Subglacial meltwater corridors (GFC). GFCs are elongated sub‐parallel tracts in the glaciated landscape where till has been eroded and in places glaciofluvial material deposited and have been mapped mostly on areas with crystalline bedrock in Canada (St‐Onge, ; Brennand and Sharpe, ; Rampton, ; Utting et al ., ; Dredge et al ., ; Sharpe et al, ; Sharpe et al, ). Glaciofluvial corridors have similar spacing to the hummock corridors in the SSU (Table ).…”
Section: Discussionmentioning
confidence: 98%
“…Another feature developed by subglacial meltwater are glaciofluvial corridors or Subglacial meltwater corridors (GFC). GFCs are elongated sub‐parallel tracts in the glaciated landscape where till has been eroded and in places glaciofluvial material deposited and have been mapped mostly on areas with crystalline bedrock in Canada (St‐Onge, ; Brennand and Sharpe, ; Rampton, ; Utting et al ., ; Dredge et al ., ; Sharpe et al, ; Sharpe et al, ). Glaciofluvial corridors have similar spacing to the hummock corridors in the SSU (Table ).…”
Section: Discussionmentioning
confidence: 98%
“…Others consist of multiple ridges, which anastomose to produce complex patterns, although these eskers are usually confined to a relatively narrow 'swath'. In places, these swathes are marked by broader corridors of glaciofluvial sediment that appear as 'bright' patches on imagery and which some workers have called 'glaciofluvial corridors ' (St-Onge, 1984;Utting, Ward, & Little, 2009). …”
Section: Esker Morphometrymentioning
confidence: 99%
“…Indeed, Maskevarri Ráhppát has similarities with anastomosing esker -Pulju moraine complex associated with subglacial Kultima fault, recently described in western Finnish Lapland (Sutinen et al, 2014b). Research in Canada has revealed that subglacial lake outbursts are able to create broad and extensive corridors of glaciofluvial landforms, eskers in particular (Rampton, 2000;Utting et al, 2009). Smaller-scale networks of anastomosing eskers have been reported from Utsjoki, some 50 m south of Maskevarri (Sutinen et al, 2009a).…”
Section: Esker Network and Periglacial Featuresmentioning
confidence: 75%
“…Paleoseismicity may have played an important role in subglacial deformation (Sutinen et al, 2009a, b), yet more detailed morphological evidence through airborne lidar would be particularly important in the future (Sutinen et al, 2014a, b). Due to the surface roughness, numerous hyperbola reflections in the ground-penetrating radar data (see, e.g., Utting et al, 2009) make the GPR structural sediment surveys challenging. Even though seismically induced deformations, seismites (Lagerbäck and Sundh, 2008;Brandes and Winsemann, 2013), are typical of soft sediments, further sedimentological studies are needed to support the neotectonic origin of ráhppát on Maskevarri fell.…”
Section: Paleoseismicitymentioning
confidence: 99%